2011
DOI: 10.1155/2011/492075
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Magic‐F1 Transgene, Involved in Muscular Hypertrophy, during Early Myogenesis

Abstract: We recently showed that Magic-F1 (Met-activating genetically improved chimeric factor 1), a human recombinant protein derived from hepatocyte growth factor/scatter factor (HGF/SF) induces muscle cell hypertrophy but not progenitor cell proliferation, both in vitro and in vivo. Here, we examined the temporal and spatial expression pattern of Magic-F1 in comparison with Pax3 (paired box gene 3) transcription factor during embryogenesis. Ranging from 9.5 to 17.5 dpc (days post coitum) mouse embryos were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…We focused our attention on identifying relevant patterns of gene expression involved in muscle hypertrophy and might therefore account for the muscle angiogenesis. In the developing muscle tissue, the expression of Magic-F1 was shown to overlap with PAX3 [10]. Here we showed that Magic-F1 could induce muscle hypertrophy and angiogenesis by both downregulating myostatin, and directly activating IGF and VEGF pathways (Fig.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…We focused our attention on identifying relevant patterns of gene expression involved in muscle hypertrophy and might therefore account for the muscle angiogenesis. In the developing muscle tissue, the expression of Magic-F1 was shown to overlap with PAX3 [10]. Here we showed that Magic-F1 could induce muscle hypertrophy and angiogenesis by both downregulating myostatin, and directly activating IGF and VEGF pathways (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…MAGIC-F1 is indeed involved in the cMet activation and in stimulating the anti-apoptotic cascade though Akt pathway activation. It has been demonstrated by previous studies that Magic-F1 transgenic mice show muscle hypertrophy and an increase in micro-capillaries during embryogenesis [9,10].…”
Section: Introductionmentioning
confidence: 93%
“…In particular, embryonic stem cells and reprogrammed fibroblasts would represent the best tool for therapy if their capacity to form teratoma could be abolished. On the other side, the use of adult progenitors is limited by the reduced plasticity of the cells, although the exposure to recombinant proteins can improve their myogenic differentiation potential [ 39 , 40 , 41 , 42 , 43 ]. So far, data on the injection of adult satellite stem cells and the influence of new neuro-muscular junction formations are limited.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that rodent or human postnatal Sk‐MABs efficiently differentiate into skeletal myotubes upon serum reduction (2%) . Notably, Sampaolesi et al showed that the intra‐arterial delivery of normal or dystrophic genetically corrected MABs to α‐sarcoglycan KO mice modeling Limb‐Girdle muscular dystrophy produced a dramatic functional amelioration of the dystrophic phenotype, thanks to their enhanced migration and homing potential compared with satellite cells, even if treated with recombinant proteins . In contrast, murine, canine, and human cardiac MABs resulting positive for pericytic markers (eg, NG2 and alkaline phosphatase [AP]) and cardiac transcription factors (TFs) such as Nkx2.5 and Gata4 rather differentiate into cardiac cells only when co‐cultured with rodent neonatal CMs or upon treatment with 5‐azacytidine, and with a variable efficiency according to the tissue source .…”
Section: Introductionmentioning
confidence: 99%